Penerapan Standar Kompetensi Profesional Guru dalam Meningkatkan Mutu Lulusan SMKS Putra Gunung Halu - Nurlaeni, Nurlaeni; H Soro, Suharyanto (Paedagogie, 2026)
This study is motivated by the need for vocational schools to produce graduates who possess technical competencies and work readiness aligned with the demands of the industrial sector. The study aims to analyze the implementation of professional teacher competency standards in improving graduate quality at SMKS Putra Gunung Halu. A descriptive qualitative approach was employed to explore teachers’ professional practices and graduates’ perceptions of learning quality. Data were collected through interviews, observations, and documentation, and were analyzed using the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing. The research focused on subject-matter mastery, variations in instructional strategies, evaluation mechanisms, and teacher professional development. The findings indicate that teachers are able to integrate subject mastery with industrial contexts, apply instructional strategies that encourage student participation, and provide evaluations and feedback that support the improvement of students’ competencies. Professional development through training programs, teacher working groups (MGMP), and certification further strengthens the implementation of professional competencies in the school. Alumni perspectives confirm that the technical skills and work readiness they acquired were shaped through the instructional practices implemented by teachers. The study concludes that the implementation of professional teacher competency standards makes a tangible contribution to strengthening graduate quality and the effectiveness of the learning process; therefore, schools are encouraged to develop sustainable teacher competency enhancement programs to ensure that graduate quality remains relevant to workforce demands.